A high flame retardant composite material and preparation method thereof

By using flame retardants such as alkyl aluminum phosphinate, nanomontmorillonite and zinc ionic ionomers in long carbon chain semi-aromatic nylon materials, the high flame retardant performance and mechanical properties of the material are improved, and the problem of poor fire resistance is solved.

CN119220094BActive Publication Date: 2025-03-18SHANDONG QIKEYUAN NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411755261.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-18
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

Long carbon chain semi-aromatic polyamide materials have poor refractory properties, and there is a risk of producing droplets and toxic gas during combustion, and flame retardant modification is required.

Method used

Aluminum alkylphosphinate is used as the main flame retardant, and nanomontmorillonite and zinc ionic ionomers are used as auxiliary flame retardants to improve the flame retardant and mechanical properties of the composite material through ionic cross-linking.

Benefits of technology

It significantly improves the flame retardant performance of long carbon chain semi-aromatic nylon composites, enhances its mechanical properties and thermal stability, avoids the melting drop phenomenon during combustion, and meets the needs of high flame retardant grades and high mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 3RAQPYZHRJQ84BNVRIOOCDA4BAT6GKIVBEVPZDB9
    Figure 3RAQPYZHRJQ84BNVRIOOCDA4BAT6GKIVBEVPZDB9
Patent Text Reader

Abstract

The invention belongs to the technical field of engineering plastics, and specifically relates to a highly flame-retardant composite material and a preparation method thereof. The composite material comprises the following components: long carbon chain semi-aromatic nylon, fiber-reinforced filler, toughening agent, alkyl aluminum phosphinate, nano-montmorillonite, zinc ion ionomer, coupling agent, lubricant, and antioxidant. Alkyl aluminum phosphinate is used as the main flame retardant, and nano-montmorillonite and zinc ion ionomer are used as auxiliary flame retardants. Nano-montmorillonite has certain adsorption properties, which can prevent the precipitation of alkyl aluminum phosphinate flame retardant during processing. Zinc ion ionomer is easier to disperse in a long carbon chain semi-aromatic nylon resin matrix than alkyl aluminum phosphinate and nano-montmorillonite, and the ionic groups contained in the zinc ion ionomer can undergo ionic crosslinking with ions in alkyl aluminum phosphinate and nano-montmorillonite, which not only improves the mechanical properties and thermal stability of the composite material, but also improves the melt viscosity, and prevents the occurrence of molten droplets during combustion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of engineering plastics, and particularly relates to a highly flame-retardant composite material and a preparation method thereof. Background Art

[0002] Polyamide is a polymer that contains amide groups in the repeating structure of the main chain of the macromolecule and can form a certain hydrogen bond density. As a thermoplastic engineering plastic, polyamide can be obtained by using lactam as the raw material through a ring-opening polymerization method, or by using diamine and dibasic acid as monomers through polycondensation. The density of polyamide products is generally around 1.01-1.62. The product weight is lighter than that of metal. It is a lightweight material and can replace metal to meet the requirements of lightweight products and cost reduction. Although nylon has good comprehensive properties, no material is perfect and has no defects. The disadvantages of nylon as an engineering plastic include high water absorption, which will lead to changes in the size and performance of the product. In addition, the ends of the main chain of the nylon macromolecule contain amino and carboxyl active groups, which will inevitably react with oxygen during processing, storage and use, resulting in poor performance. At present, there are many varieties of nylon, among which aliphatic nylon is the variety with the largest output, the widest application and large-scale industrial production, including nylon 6 and nylon 66, accounting for more than 85% of nylon products; nylon 11, nylon 1111, nylon 1212, nylon 12, nylon 46, nylon 610, nylon 612, nylon 1010 and other varieties have great market potential; in order to meet the heat resistance of some products, new varieties such as semi-aromatic nylon 6T, nylon 10T, nylon 12T and special nylon are playing an increasingly important role in occasions with harsh conditions of use. In particular, long carbon chain semi-aromatic nylons such as nylon 10T and nylon 12T have both the good processing properties of aliphatic nylon and the high temperature resistance of aromatic nylon, and have broad application prospects.

[0003] Although long-chain semi-aromatic polyamide has good mechanical properties, its fire resistance is poor. Long-chain semi-aromatic polyamide is flammable, and the molten droplets and volatile toxic gases formed by the combustion of polyamide have caused great harm to people's life and production. With the improvement of public awareness of fire prevention and the requirements of the state for fire safety in all walks of life, more and more industries need to modify polyamide materials to be flame retardant.

[0004] Flame retardant long carbon chain semi-aromatic polyamide technology covers two mainstream methods today, namely reactive flame retardant and additive flame retardant. The flame retardant is connected to the main chain or side chain of PA to become the flame retardant component contained in PA itself. This PA material is reactive flame retardant PA. The advantages of reactive flame retardant PA are relatively stable chemical composition, low toxicity, long flame retardant performance, and little effect on other properties of PA. Its disadvantages are complicated process and high cost. PA material that disperses flame retardant in polymer matrix to improve the flame retardant performance of substrate is additive flame retardant PA. Additive flame retardant PA is easy to process and requires little equipment investment. It is the most widely used technology at present. Summary of the invention

[0005] In order to improve the flame retardant properties of long carbon chain semi-aromatic nylon, the present invention provides a highly flame retardant composite material and a preparation method thereof. On the basis of improving the flame retardant properties of the long carbon chain semi-aromatic nylon composite material, its mechanical properties are also improved to a certain extent.

[0006] The technical solution of the present invention is as follows:

[0007] A highly flame retardant composite material comprising the following components in parts by weight:

[0008] 70-90 parts of long carbon chain semi-aromatic nylon, 20-30 parts of fiber reinforced filler, 10-15 parts of toughening agent, 10-15 parts of alkyl aluminum phosphinate, 4-12 parts of nano-montmorillonite, 2-4 parts of zinc ion ionomer, 0-3 parts of coupling agent, 0-3 parts of lubricant and 0-3 parts of antioxidant.

[0009] Long carbon chain semi-aromatic nylon has a lower oxygen index and poor fire resistance relative to aliphatic nylon and aromatic nylon. In order to improve the flame retardant properties of long carbon chain semi-aromatic nylon, the present invention adds alkyl phosphinate aluminum as the main flame retardant, and nano-montmorillonite and zinc ion ionomer as auxiliary flame retardants. Alkyl phosphinate aluminum has excellent flame retardant effect. After it is thermally decomposed, the decomposition product prompts the polyamide matrix to produce a solid cross-linked layer with stable structure. These dense layered structures can prevent the transfer of heat on the one hand, so that the polymer can avoid further thermal cracking, and on the other hand, they can also prevent the small molecular combustibles generated inside the polymer from escaping to the outside. However, the flame retardant effect of a single alkyl phosphinate aluminum is not good, and there is a situation of precipitation during the processing process, which affects the flame retardant effect of the product. In order to solve the problem of alkyl phosphinate aluminum, the present invention adds a certain amount of nano-montmorillonite and zinc ion ionomer. Nano-montmorillonite is a layered aluminum silicate mineral that can not only play a role in strengthening and toughening, but also the residual montmorillonite in the combustion process of long carbon chain semi-aromatic nylon will form a layer of carbon layer containing silicate on the surface of the long carbon chain semi-aromatic nylon, which can block the connection between the polymer and the outside world on the surface, delay the further transfer of volatiles generated by internal combustion to the combustion surface, and also block the external oxygen from entering the composite material. In addition, as a clay mineral filler, nano-montmorillonite has certain adsorption properties, which can prevent the precipitation of alkyl phosphinate aluminum flame retardant during processing. Further, the dosage of nano-montmorillonite is 6-9 parts; when the nano-montmorillonite material is too little, the strengthening and flame retardant effects are limited; too much is not conducive to its own dispersion, and agglomeration may occur.

[0010] Zinc ion ionomers have higher melt viscosity than other polymers. Zinc ion ionomers are easier to disperse in long carbon chain semi-aromatic nylon resin matrix than alkyl aluminum phosphinate and nano-montmorillonite. The ionic groups contained in zinc ion ionomers can undergo ionic crosslinking with ions in alkyl aluminum phosphinate and nano-montmorillonite, which not only improves the dispersion uniformity of fillers and the mechanical and thermal stability of composite materials, but also improves the melt viscosity and prevents the occurrence of molten droplets during combustion. In addition, zinc in zinc ion ionomers and aluminum in alkyl aluminum phosphinates generate corresponding metal oxides during the combustion process. The formation of metal oxides with different structures increases the density of the carbon layer, can effectively isolate oxygen and prevent the diffusion of hot gas generated by combustion, and improve the flame retardant effect.

[0011] Furthermore, the long carbon chain semi-aromatic nylon is at least one of PA9T, PA9I, PA10T, PA10I, PA11T, PA12T, and PA14T. Furthermore, the long carbon chain semi-aromatic nylon is 75-85 parts, and an appropriate amount of nylon resin can fully bond the filler and improve the mechanical properties of the composite material. The long carbon chain semi-aromatic nylon is used as the matrix resin. Compared with short-chain nylon, the long carbon chain structure can effectively disperse the amide bond, prevent excessive cross-linking of polar groups and ionomers during processing, and is not conducive to the dispersion of ionomers.

[0012] Furthermore, the fiber-reinforced filler is at least one of glass fiber, carbon fiber, and whisker.

[0013] Furthermore, the toughening agent is at least one of PP-g-MAH, PE-g-MAH, POE-g-MAH, and EPDM-g-MAH.

[0014] Furthermore, the alkyl aluminum phosphinate is diethyl aluminum phosphinate. The average particle size of the nano-montmorillonite is 50-100 nm.

[0015] Furthermore, the zinc ionomer is Surlyn resin 9320.

[0016] Furthermore, the coupling agent is at least one of KH550, KH560, KH570, and A-174.

[0017] Furthermore, the lubricant is at least one of silicone powder, talc, zinc stearate, calcium stearate, and barium stearate; and the antioxidant is at least one of hindered phenol antioxidants, phosphite antioxidants, and aromatic amine antioxidants.

[0018] On the other hand, the present invention also provides a method for preparing a highly flame retardant composite material, comprising the following steps:

[0019] (1) long carbon chain semi-aromatic nylon, toughening agent, alkyl aluminum phosphinate, nano-montmorillonite, zinc ionomer, coupling agent, lubricant, and antioxidant are uniformly mixed to obtain a premix;

[0020] (2) The premix is ​​added into a twin-screw extruder from a main feed port, and the fiber-reinforced filler is added into the twin-screw extruder from a side feed port, and the mixture is extruded and granulated to obtain a highly flame-retardant composite material.

[0021] Furthermore, the screw speed of the twin-screw extruder is 500-600 r / min, and the extrusion temperature is 300-340°C.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] 1. A highly flame-retardant composite material of the present invention uses alkyl aluminum phosphinate as a main flame retardant, and nano-montmorillonite and zinc ion ionomer as auxiliary flame retardants. Nano-montmorillonite has certain adsorption properties, which can prevent the precipitation of alkyl aluminum phosphinate flame retardant during processing. Zinc ion ionomer is easier to disperse in a long carbon chain semi-aromatic nylon resin matrix than alkyl aluminum phosphinate and nano-montmorillonite, and the ionic groups contained in the zinc ionomer can undergo ionic crosslinking with ions in alkyl aluminum phosphinate and nano-montmorillonite, which not only improves the dispersion uniformity of the filler and the mechanical and thermal stability of the composite material, but also improves the melt viscosity, preventing the occurrence of molten droplets during combustion.

[0024] 2. The highly flame-retardant composite material prepared by the present invention can simultaneously have the three performance advantages of high flame retardancy, high tensile strength and impact toughness. In addition, the main flame retardant alkyl aluminum phosphite is not easy to precipitate during the processing, is environmentally friendly and meets environmental protection requirements, and can be used in various fields with flame retardancy and high temperature resistance requirements. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is described in more detail below in conjunction with the attached table and specific embodiments, but the protection scope of the present invention is not limited to these embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] A highly flame retardant composite material comprising the following components in parts by weight:

[0028] 75 parts of long carbon chain semi-aromatic nylon PA10T, 20 parts of fiber reinforced filler, 10 parts of toughening agent, 10 parts of alkyl aluminum phosphinate, 6 parts of nano-montmorillonite, 2 parts of zinc ion ionomer, 1 part of coupling agent KH550, 1 part of lubricant, and 1 part of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is talcum powder.

[0029] Example 2

[0030] A highly flame retardant composite material comprising the following components in parts by weight:

[0031] 85 parts of long carbon chain semi-aromatic nylon PA10T, 30 parts of fiber reinforced filler, 15 parts of toughening agent, 15 parts of alkyl aluminum phosphinate, 9 parts of nano-montmorillonite, 4 parts of zinc ion ionomer, 3 parts of coupling agent KH550, 3 parts of lubricant, and 3 parts of antioxidant 1010; the fiber reinforced filler is carbon fiber; the toughening agent is PE-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is zinc stearate.

[0032] Example 3

[0033] A highly flame retardant composite material comprising the following components in parts by weight:

[0034] 85 parts of long carbon chain semi-aromatic nylon PA10T, 20 parts of fiber reinforced filler, 15 parts of toughening agent, 10 parts of alkyl aluminum phosphinate, 9 parts of nano-montmorillonite, 2 parts of zinc ion ionomer, 3 parts of coupling agent KH550, 1 part of lubricant, and 1 part of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is EPDM-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is calcium stearate.

[0035] Example 4

[0036] A highly flame retardant composite material comprising the following components in parts by weight:

[0037] 82 parts of long carbon chain semi-aromatic nylon PA10T, 27 parts of fiber reinforced filler, 14 parts of toughening agent, 13 parts of alkyl aluminum phosphinate, 8 parts of nano-montmorillonite, 3 parts of zinc ion ionomer, 2 parts of coupling agent KH550, 1 part of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is carbon fiber; the toughening agent is POE-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0038] Example 5

[0039] A highly flame retardant composite material comprising the following components in parts by weight:

[0040] 77 parts of long carbon chain semi-aromatic nylon PA10T, 22 parts of fiber reinforced filler, 11 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 7 parts of nano-montmorillonite, 2.5 parts of zinc ion ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 1 part of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PE-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0041] Example 6

[0042] A highly flame retardant composite material comprising the following components in parts by weight:

[0043] 79 parts of long carbon chain semi-aromatic nylon PA10T, 26 parts of fiber reinforced filler, 12 parts of toughening agent, 14 parts of alkyl aluminum phosphinate, 8 parts of nano-montmorillonite, 3.6 parts of zinc ion ionomer, 2 parts of coupling agent KH550, 1 part of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is calcium stearate.

[0044] Example 7

[0045] A highly flame retardant composite material comprising the following components in parts by weight:

[0046] 70 parts of long carbon chain semi-aromatic nylon PA10T, 25 parts of fiber reinforced filler, 13 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 7 parts of nano-montmorillonite, 3 parts of zinc ion ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0047] Example 8

[0048] A highly flame retardant composite material comprising the following components in parts by weight:

[0049] 90 parts of long carbon chain semi-aromatic nylon PA10T, 25 parts of fiber reinforced filler, 13 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 7 parts of nano-montmorillonite, 3 parts of zinc ion ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0050] Example 9

[0051] A highly flame retardant composite material comprising the following components in parts by weight:

[0052] 80 parts of long carbon chain semi-aromatic nylon PA10T, 25 parts of fiber reinforced filler, 13 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 4 parts of nano-montmorillonite, 3 parts of zinc ion ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0053] Example 10

[0054] A highly flame retardant composite material comprising the following components in parts by weight:

[0055] 80 parts of long carbon chain semi-aromatic nylon PA10T, 25 parts of fiber reinforced filler, 13 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 12 parts of nano-montmorillonite, 3 parts of zinc ion ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0056] Embodiment 11

[0057] A highly flame retardant composite material comprising the following components in parts by weight:

[0058] 80 parts of long carbon chain semi-aromatic nylon PA10T, 25 parts of fiber reinforced filler, 13 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 7 parts of nano-montmorillonite, 3 parts of zinc ion ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0059] Comparative Example 1

[0060] A highly flame retardant composite material comprising the following components in parts by weight:

[0061] 80 parts of long carbon chain semi-aromatic nylon PA10T, 25 parts of fiber reinforced filler, 13 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 10 parts of nano-montmorillonite, 0 parts of zinc ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; and the lubricant is barium stearate.

[0062] Comparative Example 2

[0063] A highly flame retardant composite material comprising the following components in parts by weight:

[0064] 80 parts of long carbon chain semi-aromatic nylon PA10T, 25 parts of fiber reinforced filler, 13 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 0 parts of nano-montmorillonite, 10 parts of zinc ion ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0065] Comparative Example 3

[0066] A highly flame retardant composite material comprising the following components in parts by weight:

[0067] 80 parts of long carbon chain semi-aromatic nylon PA10T, 25 parts of fiber reinforced filler, 13 parts of toughening agent, 12 parts of alkyl aluminum phosphinate, 7 parts of nano-montmorillonite, 6 parts of zinc ion ionomer, 1 part of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; the fiber reinforced filler is glass fiber; the toughening agent is PP-g-MAH; the alkyl aluminum phosphinate is diethyl aluminum phosphinate; the average particle size of the nano-montmorillonite is 80nm; the zinc ion ionomer is sarling resin 9320; and the lubricant is barium stearate.

[0068] The preparation process of the above embodiment and comparative example is the same, and specifically comprises the following steps:

[0069] (1) long carbon chain semi-aromatic nylon, toughening agent, alkyl aluminum phosphinate, nano-montmorillonite, zinc ion ionomer, coupling agent, lubricant, and antioxidant are uniformly mixed to obtain a premix;

[0070] (2) The premix is ​​added into a twin-screw extruder from a main feed port, and the fiber-reinforced filler is added into the twin-screw extruder from a side feed port, and the mixture is extruded and granulated to obtain a highly flame-retardant composite material; the screw speed of the twin-screw extruder is 500 r / min, and the extrusion temperature is 320°C.

[0071] Performance test: The highly flame-retardant composite materials obtained in the examples and comparative examples were prepared into standard samples, and the tensile strength (ISO 527-2), notched impact strength (ISO 179), and flame retardancy (UL94) of the samples were tested; and relevant performance indicators such as droplets and surface precipitation were observed. Among them, the precipitation level is divided into four levels: A, B, C, and D. From A to D, the precipitation on the surface of the product gradually increases. The test results are shown in Table 1-2 below.

[0072]

[0073] As can be seen from Table 1 and Table 2, the present invention adds alkyl phosphinate aluminum as the main flame retardant, and nano-montmorillonite and zinc ion ionomer as auxiliary flame retardants. Montmorillonite is a layered aluminum silicate mineral that can not only play a role in strengthening and toughening, but also can block external oxygen from entering the composite material, preventing the precipitation of alkyl phosphinate aluminum flame retardant during processing. The ionic groups contained in the zinc ion ionomer can undergo ionic crosslinking with the ions in the alkyl phosphinate aluminum and nano-montmorillonite, thereby improving the mechanical properties and flame retardant effect of the composite material. In addition, the zinc in the zinc ion ionomer and the aluminum in the alkyl phosphinate aluminum generate corresponding metal oxides during the combustion process. The formation of metal oxides with different structures improves the density of the carbon layer, can effectively cut off oxygen and prevent the diffusion of hot gas generated by combustion, and improves the flame retardant effect. Specifically, Example 11 and Comparative Examples 1-4 show that zinc ion ionomer is easier to disperse in the long carbon chain semi-aromatic nylon resin matrix than alkyl aluminum phosphinate and nano-montmorillonite, and the ionic groups contained in it can undergo ionic crosslinking with the ions in alkyl aluminum phosphinate and nano-montmorillonite, which not only improves the dispersion uniformity of the filler and the mechanical and thermal stability of the composite material, but also improves the melt viscosity and prevents the occurrence of molten droplets during combustion. In addition, since zinc ion ionomer plays an ionic crosslinking role in the composite material, when it is used in excessive amounts, it is not conducive to the melt processing of the composite material, resulting in a significant reduction in impact toughness.

[0074] In summary, the specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments under the concept of the present invention, but are not intended to limit the present invention; those skilled in the art can make adaptive adjustments within the concept and protection scope of the present invention.

[0075] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A highly flame retardant composite material, characterized in that: Contains the following components in parts by weight: 70-90 parts of long carbon chain semi-aromatic nylon, 20-30 parts of fiber reinforced filler, 10-15 parts of toughening agent, 10-15 parts of alkyl aluminum phosphinate, 4-12 parts of nano-montmorillonite, 2-4 parts of zinc ion ionomer, 0-3 parts of coupling agent, 0-3 parts of lubricant, 0-3 parts of antioxidant; The long carbon chain semi-aromatic nylon is PA10T.

2. A highly flame retardant composite material according to claim 1, characterized in that: The fiber-reinforced filler is at least one of glass fiber, carbon fiber, and whisker.

3. A highly flame-retardant composite material according to claim 1, characterized in that: The toughening agent is at least one of PP-g-MAH, PE-g-MAH, POE-g-MAH, and EPDM-g-MAH.

4. A highly flame-retardant composite material according to claim 1, characterized in that: The alkyl aluminum phosphinate is diethyl aluminum phosphinate.

5. The highly flame-retardant composite material according to claim 1, characterized in that: The zinc ionomer is Surlyn resin 9320.

6. The highly flame-retardant composite material according to claim 1, characterized in that: The coupling agent is at least one of KH550, KH560, KH570 and A-174.

7. The highly flame-retardant composite material according to claim 1, characterized in that: The lubricant is at least one of silicone powder, talcum powder, zinc stearate, calcium stearate, and barium stearate; the antioxidant is at least one of hindered phenol antioxidants, phosphite antioxidants, and aromatic amine antioxidants.

8. The method for preparing a highly flame-retardant composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) long carbon chain semi-aromatic nylon, toughening agent, alkyl aluminum phosphinate, nano-montmorillonite, zinc ion ionomer, coupling agent, lubricant, and antioxidant are uniformly mixed to obtain a premix; (2) The premix is ​​added into a twin-screw extruder from a main feed port, and the fiber-reinforced filler is added into the twin-screw extruder from a side feed port, and the mixture is extruded and granulated to obtain a highly flame-retardant composite material.

9. The method for preparing a highly flame-retardant composite material according to claim 8, characterized in that: The screw speed of the twin-screw extruder is 500-600r / min, and the extrusion temperature is 300-340℃.

Citation Information

Patent Citations

  • Halogen-free flame-retardation nylon 6 montmorillonite nanocomposite and preparation method thereof

    CN104211955A

  • Halogen-free flame retardant enhanced polyamide composition and product prepared from composition

    CN105838067A